Combined Baseline Strain Dyssynchrony Index and Its Acute Reduction Predicts Mid‐Term Left Ventricular Reverse Remodeling and Long‐Term Outcome after Cardiac Resynchronization Therapy. Issue 4 (18th October 2013) - Tatsumi, Kazuhiro; Tanaka, Hidekazu; Matsumoto, Kensuke; Miyoshi, Tatsuya; Hiraishi, Mana; Tsuji, Takayuki; Kaneko, Akihiro; Ryo, Keiko; Fukuda, Yuko; Norisada, Kazuko; Onishi, Tetsuari; Yoshida, Akihiro; et al.
<x xml:space="preserve">Abstract</x> The objective of this study was to test the hypothesis that combining assessment of baseline radial strain dyssynchrony index (SDI), that expressed both left ventricular (LV) dyssynchrony and residual myocardial contractility, and of acute changes in this index can yield more accurate prediction of mid‐term responders and long‐term outcome after cardiac resynchronization therapy (CRT). Radial SDI for 75 CRT patients was calculated as the average difference between peak and end‐systolic speckle tracking strain from 6 segments of the mid‐LV short‐axis view before and 8 ± 2 days after CRT. Mid‐term responder was defined as ≥15% decrease in LV end‐systolic volume 6 ± 2 months after CRT. Long‐term outcome was tracked over 5 years. Baseline radial SDI ≥6.5% is considered predictive of responder and favorable outcome, as previously reported. Acute reduction in radial SDI ≥1.5% was found to be the best predictor of mid‐term responders with CRT. Furthermore, patients with acute reductions in radial SDI ≥1.5% were associated with a significantly more favorable long‐term outcome after CRT than those with radial SDI <1.5% (log rank P < 0.001). An important findings were that baseline radial SDI ≥6.5% and acute reductions in radial SDI ≥1.5% in 42 patients were associated with the highest event‐free survival rate of 92%, whereas, 21 patients corresponding values of <6.5% and <1.5% were associated with low event‐free survival rate of 46% (log rank P < 0.001). Combined assessment of baseline radial SDI and its acute reduction after CRT may have clinical implications for predicting responders and thus patients' care.